c-Abl Inhibitors Enable Insights into the Pathophysiology and Neuroprotection in Parkinson’s Disease - Lindholm, Dan; Pham, Dan D.; Cascone, Annunziata; Eriksson, Ove; Wennerberg, Krister; Saarma, Mart (Frontiers in Aging Neuroscience, 2016)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder causing movement disabilities and several non-motor symptoms in afflicted patients. Recent studies in animal models of PD and analyses of brain specimen from PD patients revealed an increase in the level and activity of the non-receptor tyrosine kinase Abelson (c-Abl) in dopaminergic neurons with phosphorylation of protein substrates, such as α-synuclein and the E3 ubiquitin ligase, Parkin. Most significantly inhibition of c-Abl kinase activity by small molecular compounds used in the clinic to treat human leukemia have shown promising neuroprotective effects in cell and animal models of PD. This has raised hope that similar beneficial outcome may also be observed in the treatment of PD patients by using c-Abl inhibitors. Here we highlight the background for the current optimism, reviewing c-Abl and its relationship to pathophysiological pathways prevailing in PD, as well as discussing issues related to the pharmacology and safety of current c-Abl inhibitors. Clearly more rigorously controlled and well-designed trials are needed before the c-Abl inhibitors can be used in the neuroclinic to possibly benefit an increasing number of PD patients.